Increased Brain Derived Neurothropic Factor in the cerebrum and cerebellum of Rattus norvegicus newborn with exposure to Mozart's music in default sequence compared with the reversed sequence and without exposure during gestation - Agustina Hidayati; Hermanto Tri Joewono; Widjiati Widjiati (Majalah Obstetri dan Ginekologi, 2018)
Objectives: To analyze the differences in the expression of Brain Derived Neurothropic Factor (BDNF) in Rattus norvegicus cerebrum and cerebellum of newborn between those exposed to Mozart's music composition in default sequence, reverse sequence, and without exposure in the womb.Materials and Methods: Analytical laboratory experimental study with randomized post test only control group design using animal models Rattus norvegicus. The animal models were divided into three groups: control group without any exposure, the treatment groups with exposure to Mozart's music in default sequence and another group in reverse sequence since day 10 of gestation. We used a comparison test in the analysis of BDNF expression.Results: We found significant difference in BDNF expression with p value 0.004 (mean 8.98±1.31 default sequence group, 5.58±3.08 reverse sequence group, 6.80±1.95 control) in the cerebrum. We found significant difference of BDNF expression with p value 0.003 (mean 9.48±1.41 default sequence group, 6.02±3.25 reverse sequence group, 7.14±2.54 control) in the cerebellum. In cerebrum dan cerebellum we found significant difference between standard Mozart’s music and control (cere-brum p=0.018, cerebellum p=0.001), and we found significant difference between standard Mozart’s music and reverse Mozart’s music (cerebrum p=0.001, cerebellum p=0.008) and no significant difference in reverse Mozart and control (cerebrum p=0.264, cerebellum p=0.490)Conclusion: Sequence in Mozart’s music is very important in increase expression of BDNF.